PERAN AKTIVITAS SOCIAL MEDIA MARKETING TERHADAP CUSTOMER BRAND ENGAGEMENT DAN DAMPAKNYA BAGI BRAND LOYALTY DI AKUN INSTAGRAM STARBUCKS INDONESIA - Fauziyah, Atikah Nur; Yoestini, Yoestini (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this study is to explore the influence of interactive, informative, and social media marketing trends on customer brand engagement and the consequences for the brand loyalty of the @starbucksindonesia Instagram account. The population used in this study is followers and customers on accounts Instagram @starbucksindonesia in Semarang City. In taking the sample, the researcher used a purposive sampling method and distributed the Google form questionnaire as the instrument. SEM (Structural Equation Mode) with SMART PLS 3 is used in this study to carry out validity tests, reliability tests, coefficient of determination tests (Adjusted R Square) and t tests. The results of this study indicate an informative variable. The trend variable has a significant positive effect on customer brand involvement and brand loyalty except interactive. Keyword : Interactive, Interactivity, Informative, Trend, Trendy, Customer Brand Engagement, dan Brand Loyalty